The Role of Learning Guidance in Elementary Schools in Supporting Student Learning and Development: A Literature Review - Haliza Haliza; Gusriani Lise Sandra (EDOVA JOURNAL : Education for Nation Development Journal, 2025)
The purpose of this study is to examine the learning guidance provided by teachers to students at SD Negeri 27 Olo Ladang and to understand the role of learning guidance in the development of these students. In order to educate and shape future citizens according to expectations, basic education is implemented. The foundation of a nation’s progress is a high standard of education, and teachers play a vital role in helping children grow intellectually, skillfully, emotionally, morally, and spiritually. Various problems faced by students, especially in elementary schools, can disrupt their character and abilities. These issues include lack of motivation to learn, mental instability, bullying, difficulties in forming social bonds, and more. In elementary schools, guidance and counseling play an important role in helping children resolve these problems. Guidance and counseling aim to help clients develop their potential, understand themselves, and anticipate problems before they arise. However, due to teachers’ workload and the lack of specialized services for students, implementation has not been optimal. The researcher used a qualitative research approach with a case study method, employing interviews, observations, and documentation as instruments.